Fostering Student Discipline Through a Persuasive Approach - Eka Wahyu Hindarsyah; Tohirin; Andi Murniati (Ta'dib, 2024)
This research aims to identify the factors causing students' lack of discipline, understand the implementation of a persuasive approach in fostering student discipline, and identify the supporting and inhibiting factors in implementing a persuasive approach to fostering student discipline. The type of research is qualitative. There are three informants. Data collection techniques in this study include observation, interviews, and documentation. The data analysis techniques used are reduction, presentation, conclusion drawing, and verification. The research findings are as follows: The causes of students' lack of discipline include a lack of respect from students, their environment, and the crucial role of the family in shaping students' character; The implementation of the persuasive approach in fostering student discipline was carried out according to the plan agreed upon by the madrasah principal and teachers, resulting in students displaying disciplined behavior, adhering to rules, and engaging in positive activities; Supporting factors for the persuasive approach include teachers' understanding of the persuasive approach itself and the cooperation of all teachers. The inhibiting factor in student discipline is the inconsistency in understanding among school members regarding the persuasive approach. The research location is at Madrasah Aliyah Hidayatul Mubtadi'ien, Sumber Makmur, Kampar Regency.